Використання ChatGPT для створення адаптивних діалогів у відеоіграх - Трофіменко, О. О. (ХНУРЕ, 2023)
This work investigates the use of ChatGPT language model in developing adaptive dialogues for video games. The study focuses on how ChatGPT can generate NPC (non-playable character) responses based on the provided game information, specifically the player’s inventory. The integration of ChatGPT into game dialogue systems was examined. It was determined that adaptive dialogues generated by ChatGPT may provide a deeper and more convincing interaction with the game characters, improving the player’s personalized experience and immersion in the game world